Navigating the Western Academy: An Aboriginal Man's PhD Perspective - Kelly, Steven (The Australian Journal of Indigenous Education, 2020)
This paper discusses the PhD research process from my perspective as an Aboriginal man. The paper illuminates how I navigated my way through a Western academic system using an Aboriginal framework. I give insights into the dynamics at play in both academic and traditional ways of knowing, being and doing. As an Aboriginal researcher, I was intent, as many Aboriginal scholars are, on doing research that was inclusive, respectful, culturally appropriate and satisfactory to both partners. The paper is not designed as a ‘one size fits all’, but may be used as a signpost for those who choose to do research with Aboriginal people or for insights into the experiences of an Aboriginal Higher Degree by Research student and researcher.